Operational leverage activators (Costos y Gestión, 2022)
The Doctrine sustains that Operating Leverage is activated by a variation in the level of use of the productive structure owned by the company. This gives rise to an all-encompassing conception and extremely rigid towards the company.This work shows how the network organization improves the profitability of agricultural companies, counteracts the Law of Diminishing Marginal Returns, and the increase in risk; it was proposed to determine if there are other activators by analyzing said model. Concluding that there are other activators such as the hiring of third-party factors, changes in the price and mix of products, in variable costs, technical advances in inputs, and in processes.Each company has its own leverage matrix, with its own triggers, each with its own potential. This is determined by the magnitude of the variation of the activator and its importance in the structure of the Total Marginal Contribution.A model is proposed that, considering each concept of income and variable cost, makes it possible to identify the activators and quantify their effects; allowing for sensitization. Showing that the productive structures have activators that, when used, can make them more ductile, being suitable for evaluating the possibilities provided by the network production system.
Keywords: operating leverage; leverage; agricultural company; network production